Effects of ginkgo leaf tablet on the pharmacokinetics of rosiglitazone in rats and its potential mechanism - Xueting Xing; Mengzhu Kong; Qiaoyu Hou; Jiaqi Li; Wen Qian; Xijing Chen; Hanhan Li; Changqing Yang (Taylor & Francis Group, 2022)
Context Ginkgo leaf tablet (GLT), a traditional Chinese herbal formula, is often combined with rosiglitazone (ROS) for type 2 diabetes mellitus treatment. However, the drug-drug interaction between GLT and ROS remains unknown.Objective To investigate the effects of GLT on the pharmacokinetics of ROS and its potential mechanism.Materials and methods The pharmacokinetics of 10 mg/kg ROS with 100/200 mg/kg GLT as single-dose and 10-day multiple-dose administration were investigated in Sprague-Dawley rats. In vitro, the effects of GLT on the activity of CYP2C8 and CYP2C9 were determined in recombinant human yeast microsomes and rat liver microsomes with probe substrates.Results The t1/2 of ROS increased from 2.14 ± 0.38 (control) to 2.79 ± 0.37 (100 mg/kg) and 3.26 ± 1.08 h (200 mg/kg) in the single-dose GLT administration. The AUC0-t (139.69 ± 45.46 vs. 84.58 ± 39.87 vs. 66.60 ± 15.90 h·μg/mL) and t1/2 (2.75 ± 0.70 vs. 1.99 ± 0.44 vs. 1.68 ± 0.35 h) decreased significantly after multiple-dose GLT treatment. The IC50 values of quercetin, kaempferol, and isorhamnetin, GLT main constituents, were 9.32, 7.67, and 11.90 μmol/L for CYP2C8, and 27.31, 7.57, and 4.59 μmol/L for CYP2C9. The multiple-dose GLT increased rat CYP2C8 activity by 44% and 88%, respectively.Discussion and conclusions The metabolism of ROS is attenuated in the single dose of GLT by inhibiting CYP2C8 and CYP2C9 activity, and accelerated after the multiple-dose GLT treatment via inducing CYP2C8 activity in rats, indicating that the clinical dose of ROS should be adjusted when co-administrated with GLT.